The power of social media in the decision-making of current and future professionals: a crucial analysis in the digital era - Jackeline Andrea Macías Urrego; Vanessa García Pineda; Luz Alexandra Montoya Restrepo (Cogent Business & Management, 2024)
This study aims to analyze the impact of social media on pre‑purchase decision‑making among both current and future professionals. For this analysis, information obtained from a previous bibliometric study was used. From this study, 6 research questions and 3 hypotheses were developed, driven by 8 variables. A 14‑question survey was administered to 214 students and graduates from various programs in Medellín, Colombia. Results indicated that 92.5% of participants actively used social media for information before making purchase decisions, with Instagram, YouTube, and Facebook as preferred platforms. Instagram was notably popular among those aged 18–25, while Facebook and YouTube had a more uniform appeal across age groups. Additionally, participants also considered reviews on platforms like Google Reviews, Amazon, and Mercado Libre. The findings suggest no significant age‑based differences in platform preferences, implying that personal factors beyond age influence social media choice. Furthermore, the use of social networks to research products or services is a common practice among students and professionals, regardless of their educational level. In conclusion, this study indeed offers valuable insights for organizations to refine their marketing strategies and captivate customers through the quality, impact, and dissemination of the content they post on social media.
Keywords: 650; Social media; purchase decision; consumer behavior; online marketing; digital influence